A Fuzzy-PD Controller to Improve the Performance of HVDC System - Mohammad Sarvi; Majid Keshmiri (International Journal of Applied Power Engineering (IJAPE), 2013)
In this paper, a fuzzy self adjustment controller has been designed for using in control of a high voltage direct current (HVDC) system. Fuzzy logic method via fuzzy rules based on simple experimental logical proofs, selects the coefficient of PD controller. In order to investigate the performance and accuracy of the proposed control method, a Cigre system is considered and analyzed. The proposed fuzzy - PD controller is compared with conventional PD controller. To achieve this purpose, the operations of designed controllers are investigated for different conditions. Fuzzy controllers used to control of inverter and rectifier converters, improve significantly system responses and performances as well as DC power recovering, especially on hard faults. The HVDC control system with fuzzy controllers in soft faults and variations with small amplitude, are similar conventional control, but on hard faults and variation with large amplitude, the performances are improved in compare with conventional control.